Pre-transplant malignancy is associated with increased risk of de novo malignancy post-lung transplantation. (June 2022) - Sekowski, Viktor; Jackson, Kathy; Halloran, Kieran; Varughese, Rhea; Nagendran, Jayan; Weinkauf, Justin; Lien, Dale; Hirji, Alim
Abstract: Background: At least 20% of lung transplant recipients will be diagnosed with a malignancy within 5 years of transplant. Transplant candidates with a history of pre-transplant malignancy must meet remission criteria before listing to minimize the risk of recurrence, however these patients may have an intrinsic predisposition to developing subsequent cancers which can be amplified by immunosuppression. We assessed whether pre-transplant malignancy was associated with an increased risk of developing malignancy of any type after lung transplant. Methods: We conducted a single centre retrospective cohort study of patients undergoing lung transplant between January 2006 and December 2017. We used a proportional hazards regression model to test whether preTM was associated with the risk of developing one or more postTM after lung transplant, adjusted for known cancer risk factors. Results: 497 adult patients underwent lung transplantation during the study period and 26 (5.2%) had pre-transplant malignancies. Out of 29 pre-transplant cancer diagnoses, prostate cancer was the most common (17.2%), followed by breast cancer and basal cell carcinoma (13.8% each). 108 (22%) patients developed post-transplant malignancy with a total of 328 cancer diagnoses. The most common post-transplant malignancy was non-melanoma skin cancer (86.3%), followed by solid organ cancers (7.6%). Pre-transplant malignancy was associated with an adjusted HR of 3.24 (95% CI 1.71 to 6.14, p < 0.001) for the development of post-transplant malignancy. Recurrence of the pre-transplant malignancy only occurred in 3 patients post-transplant. Conclusions: History of pre-transplant malignancy was associated with a more than three times likelihood of development of a post-transplant malignancy compared to recipients without a previous history of cancer, the majority being unrelated to the initial malignancy. These findings highlight the importance of frequent cancer surveillance in lung transplant recipients, especially in those with a history of pre-transplant malignancy. Highlights: Post-transplant malignancy is a common complication facing lung transplant recipients. Pre-lung transplant malignancy increases the risk of post-transplant malignancy. Most post-lung transplant malignancies are de novo, unrelated to previous malignancy. The vast majority of post-lung transplant malignancies are cutaneous. Vigilant cancer screening is necessary in the care of lung transplant recipients.